Transition Signal Analysis in Undergraduate Theses: An Overview - Bantulu, Yusna; Suto, Elvriza Vadyla Marchena; Mestari, Sri Agriyanti (Ideas Publishing, 2024)
Transition signals is one of the main important things in composing a coherent paragraph; in fact, many students still feel struggle to apply them in their academic writing. Therefore, this research is conducted in order to provide a comprehensive overview of how current students use transition signals in their undergraduate thesis. This research is conducted by using descriptive qualitative method. The data are obtained from nine findings and discussion chapters on undergraduate thesis of English department students. The data are classified based on the types of transition signals by Oshima and Hogue (2006). The result revealed that all types of transition signals are existed in undergraduate thesis, those are transition signals for chronological order, order of importance, additional idea, cause and effect, comparison and contrast, giving example, and conclusion. The type of transition signals that most frequently used is transition signals for addition whereas the type of transition as the least used is transition signals for order of importance. Also, the type of transition signals that most incorrectly used is transition signals for chronological order